SPORT AS SOCIO-EDUCATIONAL PHENOMENON - Adib Đozić, (Sport Scientific And Practical Aspects, 2025)
Sport is a socio-educational phenomenon. Isn’t it something that is a perceptional and scientific thought interested in? Is it necessary for a teacher, sportsman, coach, pedagogue, social psychologist, sociologist, pupils and students to acquire knowledge of sport, its social reality and perception of it as an educational fact? These days, sport has become a part of everyday life, although much more as a entertainment and ‘’waste of time’’ for sport audience on sport fields as well as in personal homes in front of television sets and radios, than it has become an integral part of educational and upbringing practice of everyday life. Why? Answer on this question should be looked for in the framework of understanding sport as a scientific, social and educational phenomenon. To achieve this, it is necessary, first of all in BH sociological studies, to approach more intensively to development of anthropology of sport, to foundation and development of sociology and pedagogy of sport as well as to development of theory of sport. Within scientific context in Bosnia and Herzegovina, it is evident that we are at the beginning of developing, in sociological thought, a sociology of sport, as a sub-sociological scientific discipline, which will, in scientifically relevant way, explain sports and sport activity as a social and educational phenomenon and, on the basis of that knowledge, realize sport reality as an educational activity, too. The aim of this work is to initiate development of sociological examination of sport activities as social contents, as well as contents of educational activities on all levels of educational process.